Indicators to evaluate the labor insertion of people with disabilities in conventional companies in Spain: A Delphi study - Rafael Sánchez-Arizcuren; Esperanza García-Uceda; Bárbara Oliván-Blázquez (PLoS ONE, 2025)
Introduction The level of labor integration of people with disability (PwD) is notably lower than that of people without disabilities. In order to evaluate the success of the labor market integration of people with disabilities, it is necessary to establish a series of indicators that go beyond hiring rates. Hence, the objective of this study is to develop a list of indicators with their specified individual weight that will serve to evaluate the success of the labor market insertion of PwD in conventional companies. Methodology The Delphi method was used. In Phase 1, an open-ended questionnaire was distributed to 48 human resources and disability experts. From this qualitative analysis, a list of 52 indicators was drawn up and the experts were asked to evaluate their importance using a scale from 0 to 10 points. The convergence of opinion was obtained in the third phase. To evaluate the degree of stability of the experts’ responses in the different phases, the Wilcoxon test was applied. Finally, a factor analysis was carried out in relation to the indicators. Results After the development of the three phases and the factor analysis, a list of 26 indicators was obtained to measure the success of inclusive employability, structured in four factors: Work Performance, Labor Management, Social and Organizational Impact, Competency Assessment. Conclusions This project has provided a list of indicators that can be the basis for the creation of a scale to assess the successful integration of people with disabilities in the conventional company.